EFFECT OF CANE USAGE ON CLINICAL AND GAIT CHARACTERISTICS OF PATIENTS WITH OSTEARTHRITIS OF KNEE - Güneş Yavuzer; Süreyya Ergin (Archives of Rheumatology, 2002)
This study was designed to investigate the effects of cane usage, for three weeks, on pain severity, stiffness, physical functioning and gait characteristics of patients with osteoarthritis of knee. Fifteen patients (9 women, 6 men) with an average age of 53.1 ± 9.7 years, having osteoarthritis of knee but free of symptoms from their hips or ankle joints were enrolled into the study. Sociodemographic and clinical characteristics were documented. The outcome parameters, measured before and after three weeks ‘ cane usage, were Western Ontario and Mc Master University Osteoartritis Index and time-distance (walking velocity, step time, step length), kinematic (joint rotation angles of knee in sagittal and coronal planes) and kinetic (adductor and extensor moments of knee and scaled vertical ground reaction forces) characteristics of gait using a three-dimensional computerized gait analysis system. After the first assessment, all the patients were instructed to use a standard adjustable aluminum cane for three weeks. There was not a significant difference in assessed parameters after the usage of cane. A slight decrease in walking velocity was observed after the usage of a cane from 1.0 ± 0.06 m/sec to 0.96 ± 0.04 m/sec. However, the adductor and extensor moments, and vertical ground reaction forces which are the major determinants of knee loading did not differ with cane usage. In conclusion, this study could not show a significant effect of cane usage for three weeks on pain severity, stiffness, physical functioning, and kinematic and kinetic gait characteristics of patients with osteoarthritis of knee.